Ø§Ø³Ø¨Ø§Ø¨ Ø¶Ø¹Ù Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ Ù…Ø§Ø¯Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø¬Ø§Ù…Ø¹Ø© Ø§Ù„Ù‡Ø¯Ø§ÙŠØ© ØªØ§Ø³ÙŠÙƒÙ…Ù„Ø§ÙŠØ§ - Gumelar, Agung (UIN Sumatera Utara Medan, 2020)
Abstrac: The goal of this research is to understanding the cause of student weakness in reading Arabic. This research was analyzed with the qualitative research with observation, interviewing, documentation, and triangulation to identify the major cause of difficulties ofreading Arabic in STIT al-Hidayah and its solution. Based on some data that has found during the research, it came with results thatthe major cause of difficulties in reading Arabic was occur because: distance balance of reading skill that cannot be handled, lack use in teaching instruments, the books not suitable for Arabic reading practices, mixed reading, the absences of students during the Arabic reading class, lecturers have a little experiences to improve reading skill, the lecturers skill not adequate well. the general solution to answer this difficulties is making reading skills activities that suitable for them, use the teaching instruments, use the suitable books, minimize the mixed reading, minimize the absences of students,inprove lecturers reading skills in Arabic.